Effect of Calcium on Two-Dimensional Morphology and Photocatalytic Properties of Tin Oxide Nanoparticles - Vallimeena, S.; Helina, B. (Asian Journal of Chemistry, 2023)
A simple, inexpensive and environmental friendly co-precipitation approach has been used to synthesize calcium doped SnO2 photocatalysts effectively with a high surface area. The X-ray diffraction (XRD), scanning electron microscopy (SEM), Raman spectroscopy, Fourier transform infrared (FTIR), ultraviolet-visible (UV-Vis) and photoluminescence (PL) spectroscopies all have been used to characterize the structural, morphological, optical and electrochemical properties of the prepared SnO2:Ca nanoparticles. Both crystallized SnO2 and SnO2:Ca nanoparticles have tetragonal geometry. The structure and defects of the prepared sample were verified by the Raman spectra. The redshift in optical investigations confirmed the reduction in the optical band gap with increasing Ca content. The photocatalytic decomposition of methylene blue were also carried out using prepared SnO2:Ca nanoparticles in visible light. In particular, when compared to other samples, the SnO2:Ca (7 wt.%) nanoplates show the best photocatalytic activity which is confirmed from the low photoluminescence spectrum. By evenly dispersing Ca atoms across the SnO2 matrix, the band gap may be significantly lowered, allowing for more effective separation of photogenerated electron-hole pairs and, in turn, more visible-light absorption. The charge separation efficacy of SnO2:Ca (7 wt.%) nanoplates has been confirmed by EIS measurements.